Library prosa.util.sum
From mathcomp Require Import ssreflect ssrbool eqtype ssrnat seq fintype bigop path.
Require Export prosa.util.notation.
Require Export prosa.util.rel.
Require Export prosa.util.nat.
Section SumsOverSequences.
Require Export prosa.util.notation.
Require Export prosa.util.rel.
Require Export prosa.util.nat.
Section SumsOverSequences.
Consider any type I with a decidable equality ...
... and assume we are given a sequence ...
... and a predicate P.
First, we will show some properties of the sum performed over a single function
yielding natural numbers.
Consider any function that yields natural numbers.
We start showing that having every member of r equal to zero is equivalent to
having the sum of all the elements of r equal to zero, and vice-versa.
Lemma sum_nat_eq0_nat :
(\sum_(i <- r | P i) F i == 0) = all (fun x ⇒ F x == 0) [seq x <- r | P x].
Proof.
elim: r ⇒ [|x r' IH]; rewrite ?big_nil//= big_cons.
by case: ifP; rewrite ?addn_eq0 IH.
Qed.
(\sum_(i <- r | P i) F i == 0) = all (fun x ⇒ F x == 0) [seq x <- r | P x].
Proof.
elim: r ⇒ [|x r' IH]; rewrite ?big_nil//= big_cons.
by case: ifP; rewrite ?addn_eq0 IH.
Qed.
In the same way, if at least one element of r is not zero, then the sum of all
elements of r must be strictly positive, and vice-versa.
Lemma sum_nat_gt0 :
(0 < \sum_(i <- r | P i) F i) = has (fun x ⇒ 0 < F x) [seq x <- r | P x].
Proof.
apply/negb_inj; rewrite lt0n negbK sum_nat_eq0_nat -all_predC.
by apply/eq_all ⇒ ?; rewrite /= lt0n negbK.
Qed.
(0 < \sum_(i <- r | P i) F i) = has (fun x ⇒ 0 < F x) [seq x <- r | P x].
Proof.
apply/negb_inj; rewrite lt0n negbK sum_nat_eq0_nat -all_predC.
by apply/eq_all ⇒ ?; rewrite /= lt0n negbK.
Qed.
Next, we show that if a number a is not contained in r, then filtering or not
filtering a when summing leads to the same result.
Lemma sum_notin_rem_eqn a :
a \notin r →
\sum_(x <- r | P x && (x != a)) F x = \sum_(x <- r | P x) F x.
Proof.
move⇒ a_notin_r; rewrite [LHS]big_seq_cond [RHS]big_seq_cond.
apply: eq_bigl ⇒ x; case xinr: (x \in r) ⇒ //=.
have [xa|] := eqP; last by rewrite andbT.
by move: xinr a_notin_r; rewrite xa ⇒ →.
Qed.
a \notin r →
\sum_(x <- r | P x && (x != a)) F x = \sum_(x <- r | P x) F x.
Proof.
move⇒ a_notin_r; rewrite [LHS]big_seq_cond [RHS]big_seq_cond.
apply: eq_bigl ⇒ x; case xinr: (x \in r) ⇒ //=.
have [xa|] := eqP; last by rewrite andbT.
by move: xinr a_notin_r; rewrite xa ⇒ →.
Qed.
We prove that if any element of r is bounded by constant c,
then the sum of the whole set is bounded by c × size r.
Lemma sum_majorant_constant c :
(∀ a, a \in r → P a → F a ≤ c) →
\sum_(j <- r | P j) F j ≤ c × (size [seq j <- r | P j]).
Proof.
move⇒ Fa_le_c.
rewrite -sum1_size big_filter big_distrr/= muln1.
rewrite big_seq_cond [X in _ ≤ X]big_seq_cond.
apply: leq_sum ⇒ i /andP[ir Pi]; exact: Fa_le_c.
Qed.
(∀ a, a \in r → P a → F a ≤ c) →
\sum_(j <- r | P j) F j ≤ c × (size [seq j <- r | P j]).
Proof.
move⇒ Fa_le_c.
rewrite -sum1_size big_filter big_distrr/= muln1.
rewrite big_seq_cond [X in _ ≤ X]big_seq_cond.
apply: leq_sum ⇒ i /andP[ir Pi]; exact: Fa_le_c.
Qed.
Next, we show that the sum of the elements in r respecting P can
be obtained by removing from the total sum over r the sum of the elements
in r not respecting P.
Lemma sum_pred_diff:
\sum_(r <- r | P r) F r = \sum_(r <- r) F r - \sum_(r <- r | ~~ P r) F r.
Proof. by rewrite [X in X - _](bigID P)/= addnK. Qed.
End SumOfOneFunction.
\sum_(r <- r | P r) F r = \sum_(r <- r) F r - \sum_(r <- r | ~~ P r) F r.
Proof. by rewrite [X in X - _](bigID P)/= addnK. Qed.
End SumOfOneFunction.
In this section, we show some properties of the sum performed over two different functions.
Consider three functions that yield natural numbers.
Assume that E2 dominates E1 in all the points contained in the set r and respecting
the predicate P. We prove that, if we sum both function over those points, then the sum
of E2 will dominate the sum of E1.
Lemma leq_sum_seq :
(∀ i, i \in r → P i → E1 i ≤ E2 i) →
\sum_(i <- r | P i) E1 i ≤ \sum_(i <- r | P i) E2 i.
Proof.
move⇒ le; rewrite big_seq_cond [X in _ ≤ X]big_seq_cond.
apply: leq_sum ⇒ i /andP[]; exact: le.
Qed.
(∀ i, i \in r → P i → E1 i ≤ E2 i) →
\sum_(i <- r | P i) E1 i ≤ \sum_(i <- r | P i) E2 i.
Proof.
move⇒ le; rewrite big_seq_cond [X in _ ≤ X]big_seq_cond.
apply: leq_sum ⇒ i /andP[]; exact: le.
Qed.
In the same way, if E1 equals E2 in all the points considered above, then also the two
sums will be identical.
Lemma eq_sum_seq:
(∀ i, i \in r → P i → E1 i == E2 i) →
\sum_(i <- r | P i) E1 i == \sum_(i <- r | P i) E2 i.
Proof.
move⇒ eqE; apply/eqP; rewrite -big_filter -[RHS]big_filter.
apply: eq_big_seq ⇒ x; rewrite mem_filter ⇒ /andP[Px xr]; exact/eqP/eqE.
Qed.
(∀ i, i \in r → P i → E1 i == E2 i) →
\sum_(i <- r | P i) E1 i == \sum_(i <- r | P i) E2 i.
Proof.
move⇒ eqE; apply/eqP; rewrite -big_filter -[RHS]big_filter.
apply: eq_big_seq ⇒ x; rewrite mem_filter ⇒ /andP[Px xr]; exact/eqP/eqE.
Qed.
Assume that P1 implies P2 in all the points contained in
the set r. We prove that, if we sum both functions over those
points, then the sum of E conditioned by P2 will dominate
the sum of E conditioned by P1.
Lemma leq_sum_seq_pred:
(∀ i, i \in r → P1 i → P2 i) →
\sum_(i <- r | P1 i) E i ≤ \sum_(i <- r | P2 i) E i.
Proof.
move⇒ imp; rewrite [X in _ ≤ X](bigID P1)/=.
rewrite big_seq_cond [X in _ ≤ X + _]big_seq_cond.
rewrite (eq_bigl (fun i ⇒ [&& i \in r, P2 i & P1 i])) ?leq_addr// ⇒ i.
by case ir: (i \in r); case P1i: (P1 i); rewrite ?andbF //= (imp i).
Qed.
End SumOfTwoFunctions.
End SumsOverSequences.
(∀ i, i \in r → P1 i → P2 i) →
\sum_(i <- r | P1 i) E i ≤ \sum_(i <- r | P2 i) E i.
Proof.
move⇒ imp; rewrite [X in _ ≤ X](bigID P1)/=.
rewrite big_seq_cond [X in _ ≤ X + _]big_seq_cond.
rewrite (eq_bigl (fun i ⇒ [&& i \in r, P2 i & P1 i])) ?leq_addr// ⇒ i.
by case ir: (i \in r); case P1i: (P1 i); rewrite ?andbF //= (imp i).
Qed.
End SumOfTwoFunctions.
End SumsOverSequences.
For technical (and temporary) reasons related to the proof style, the next
two lemmas are stated outside of the section, but conceptually make use of a
similar context.
First, we observe that summing over a subset of a given sequence, if all
summands are natural numbers, cannot yield a larger sum.
Lemma leq_sum_subseq (I : eqType) (r r' : seq I) (P : pred I) (F : I → nat) :
subseq r r' →
\sum_(i <- r | P i) F i ≤ \sum_(i <- r' | P i) F i.
Proof.
elim: r r' ⇒ [|x r IH] r'; first by rewrite big_nil.
elim: r' ⇒ [//|x' r' IH'] /=; have [<- /IH {}IH|_ /IH' {}IH'] := eqP.
- by rewrite !big_cons; case: (P x); rewrite // leq_add2l.
- rewrite [X in _ ≤ X]big_cons; case: (P x') ⇒ //.
exact: leq_trans (leq_addl _ _).
Qed.
subseq r r' →
\sum_(i <- r | P i) F i ≤ \sum_(i <- r' | P i) F i.
Proof.
elim: r r' ⇒ [|x r IH] r'; first by rewrite big_nil.
elim: r' ⇒ [//|x' r' IH'] /=; have [<- /IH {}IH|_ /IH' {}IH'] := eqP.
- by rewrite !big_cons; case: (P x); rewrite // leq_add2l.
- rewrite [X in _ ≤ X]big_cons; case: (P x') ⇒ //.
exact: leq_trans (leq_addl _ _).
Qed.
Second, we repeat the above observation that summing a superset of natural
numbers cannot yield a lesser sum, but phrase the claim differently.
Requiring the absence of duplicate in r is a simple way to guarantee that
the set inclusion r ≤ rs implies the actually required multiset
inclusion.
Lemma leq_sum_sub_uniq (I : eqType) (r : seq I) (F : I → nat) (rs : seq I) :
uniq r → {subset r ≤ rs} →
\sum_(i <- r) F i ≤ \sum_(i <- rs) F i.
Proof.
move⇒ uniq_r sub_r_rs.
rewrite [X in _ ≤ X](bigID (fun x ⇒ x \in r))/=.
apply: leq_trans (leq_addr _ _).
rewrite (perm_big (undup [seq x <- rs | x \in r])).
- rewrite -filter_undup big_filter_cond/=.
under eq_bigl ⇒ ? do rewrite andbT; exact/leq_sum_subseq/undup_subseq.
- apply: uniq_perm; rewrite ?undup_uniq// ⇒ x.
rewrite mem_undup mem_filter.
by case xinr: (x \in r); rewrite // (sub_r_rs _ xinr).
Qed.
uniq r → {subset r ≤ rs} →
\sum_(i <- r) F i ≤ \sum_(i <- rs) F i.
Proof.
move⇒ uniq_r sub_r_rs.
rewrite [X in _ ≤ X](bigID (fun x ⇒ x \in r))/=.
apply: leq_trans (leq_addr _ _).
rewrite (perm_big (undup [seq x <- rs | x \in r])).
- rewrite -filter_undup big_filter_cond/=.
under eq_bigl ⇒ ? do rewrite andbT; exact/leq_sum_subseq/undup_subseq.
- apply: uniq_perm; rewrite ?undup_uniq// ⇒ x.
rewrite mem_undup mem_filter.
by case xinr: (x \in r); rewrite // (sub_r_rs _ xinr).
Qed.
We continue establishing properties of sums over sequences, but start a new
section here because some of the below proofs depend lemmas in the preceding
section in their full generality.
Consider any type I with a decidable equality ...
... and assume we are given a sequence ...
... and a predicate P.
Consider two functions that yield natural numbers.
First, as an auxiliary lemma, we observe that, if E1 j is less than E2
j for some element j involved in a summation (filtered by P), then
the corresponding totals are not equal.
Lemma ltn_sum_leq_seq j :
j \in r →
P j →
E1 j < E2 j →
(∀ i, i \in r → P i → E1 i ≤ E2 i) →
\sum_(x <- r | P x) E1 x < \sum_(x <- r | P x) E2 x.
Proof.
move⇒ jr Pj ltj le.
rewrite (big_rem j)// [X in _ < X](big_rem j)//= Pj -addSn leq_add//.
apply: leq_sum_seq ⇒ i /mem_rem; exact: le.
Qed.
j \in r →
P j →
E1 j < E2 j →
(∀ i, i \in r → P i → E1 i ≤ E2 i) →
\sum_(x <- r | P x) E1 x < \sum_(x <- r | P x) E2 x.
Proof.
move⇒ jr Pj ltj le.
rewrite (big_rem j)// [X in _ < X](big_rem j)//= Pj -addSn leq_add//.
apply: leq_sum_seq ⇒ i /mem_rem; exact: le.
Qed.
Next, we prove that if for any element i of a set r the following two
statements hold (1) E1 i is less than or equal to E2 i and (2) the sum
E1 x_1, ..., E1 x_n is equal to the sum of E2 x_1, ..., E2 x_n, then
E1 x is equal to E2 x for any element x of xs.
Lemma eq_sum_leq_seq :
(∀ i, i \in r → P i → E1 i ≤ E2 i) →
\sum_(x <- r | P x) E1 x == \sum_(x <- r | P x) E2 x
= all (fun x ⇒ E1 x == E2 x) [seq x <- r | P x].
Proof.
move⇒ le; rewrite all_filter; case aE: all.
apply: eq_sum_seq ⇒ i ir Pi; move: aE ⇒ /allP/(_ i ir)/implyP; exact.
have [j /andP[jr Pj] ltj] : exists2 j, (j \in r) && P j & E1 j < E2 j.
have /negbT := aE; rewrite -has_predC ⇒ /hasP[j jr /=].
rewrite negb_imply ⇒ /andP[Pj neq].
- by ∃ j; first exact/andP; rewrite ltn_neqAle neq le.
- by apply/negbTE; rewrite neq_ltn (ltn_sum_leq_seq j).
Qed.
End SumsOverSequences.
(∀ i, i \in r → P i → E1 i ≤ E2 i) →
\sum_(x <- r | P x) E1 x == \sum_(x <- r | P x) E2 x
= all (fun x ⇒ E1 x == E2 x) [seq x <- r | P x].
Proof.
move⇒ le; rewrite all_filter; case aE: all.
apply: eq_sum_seq ⇒ i ir Pi; move: aE ⇒ /allP/(_ i ir)/implyP; exact.
have [j /andP[jr Pj] ltj] : exists2 j, (j \in r) && P j & E1 j < E2 j.
have /negbT := aE; rewrite -has_predC ⇒ /hasP[j jr /=].
rewrite negb_imply ⇒ /andP[Pj neq].
- by ∃ j; first exact/andP; rewrite ltn_neqAle neq le.
- by apply/negbTE; rewrite neq_ltn (ltn_sum_leq_seq j).
Qed.
End SumsOverSequences.
In this section, we prove a variety of properties of sums performed over ranges.
First, we prove that the sum of Δ ones is equal to Δ .
Lemma sum_of_ones:
∀ t Δ,
\sum_(t ≤ x < t + Δ) 1 = Δ.
Proof. by move⇒ t Δ; rewrite big_const_nat iter_addn_0 mul1n addKn. Qed.
∀ t Δ,
\sum_(t ≤ x < t + Δ) 1 = Δ.
Proof. by move⇒ t Δ; rewrite big_const_nat iter_addn_0 mul1n addKn. Qed.
Next, we show that a sum of natural numbers equals zero if and only
if all terms are zero.
Lemma big_nat_eq0 m n F:
\sum_(m ≤ i < n) F i = 0 ↔ (∀ i, m ≤ i < n → F i = 0).
Proof.
split.
- rewrite /index_iota ⇒ /eqP.
rewrite sum_nat_eq0_nat filter_predT ⇒ /allP ZERO i.
rewrite -mem_index_iota /index_iota ⇒ IN.
by apply/eqP; apply ZERO.
- move⇒ ZERO.
have→ : \sum_(m ≤ i < n) F i = \sum_(m ≤ i < n) 0 by apply eq_big_nat.
exact: big1_eq.
Qed.
\sum_(m ≤ i < n) F i = 0 ↔ (∀ i, m ≤ i < n → F i = 0).
Proof.
split.
- rewrite /index_iota ⇒ /eqP.
rewrite sum_nat_eq0_nat filter_predT ⇒ /allP ZERO i.
rewrite -mem_index_iota /index_iota ⇒ IN.
by apply/eqP; apply ZERO.
- move⇒ ZERO.
have→ : \sum_(m ≤ i < n) F i = \sum_(m ≤ i < n) 0 by apply eq_big_nat.
exact: big1_eq.
Qed.
Moreover, the fact that the sum is smaller than the range of the summation
implies the existence of a zero element.
Lemma sum_le_summation_range:
∀ f t Δ,
\sum_(t ≤ x < t + Δ) f x < Δ →
∃ x, t ≤ x < t + Δ ∧ f x = 0.
Proof.
induction Δ; intros; first by rewrite ltn0 in H.
destruct (f (t + Δ)) eqn: EQ.
{ ∃ (t + Δ); split; last by done.
by apply/andP; split; [rewrite leq_addr | rewrite addnS ltnS]. }
{ move: H; rewrite addnS big_nat_recr //= ?leq_addr // EQ addnS ltnS; move ⇒ H.
feed IHΔ.
{ by apply leq_ltn_trans with (\sum_(t ≤ i < t + Δ) f i + n); first rewrite leq_addr. }
move: IHΔ ⇒ [z [/andP [LE GE] ZERO]].
∃ z; split; last by done.
apply/andP; split; first by done.
by rewrite ltnS ltnW. }
Qed.
∀ f t Δ,
\sum_(t ≤ x < t + Δ) f x < Δ →
∃ x, t ≤ x < t + Δ ∧ f x = 0.
Proof.
induction Δ; intros; first by rewrite ltn0 in H.
destruct (f (t + Δ)) eqn: EQ.
{ ∃ (t + Δ); split; last by done.
by apply/andP; split; [rewrite leq_addr | rewrite addnS ltnS]. }
{ move: H; rewrite addnS big_nat_recr //= ?leq_addr // EQ addnS ltnS; move ⇒ H.
feed IHΔ.
{ by apply leq_ltn_trans with (\sum_(t ≤ i < t + Δ) f i + n); first rewrite leq_addr. }
move: IHΔ ⇒ [z [/andP [LE GE] ZERO]].
∃ z; split; last by done.
apply/andP; split; first by done.
by rewrite ltnS ltnW. }
Qed.
Next, we prove that the summing over the difference of two functions is
the same as summing over the two functions separately, and then taking the
difference of the two sums. Since we are using natural numbers, we have to
require that one function dominates the other in the summing range.
Lemma sumnB_nat m n F G :
(∀ i, m ≤ i < n → F i ≥ G i) →
\sum_(m ≤ i < n) (F i - G i) =
(\sum_(m ≤ i < n) (F i)) - (\sum_(m ≤ i < n) (G i)).
Proof.
move⇒ le.
rewrite big_nat_cond [X in X - _]big_nat_cond [X in _ - X]big_nat_cond.
rewrite sumnB// ⇒ i; rewrite andbT; exact: le.
Qed.
End SumsOverRanges.
(∀ i, m ≤ i < n → F i ≥ G i) →
\sum_(m ≤ i < n) (F i - G i) =
(\sum_(m ≤ i < n) (F i)) - (\sum_(m ≤ i < n) (G i)).
Proof.
move⇒ le.
rewrite big_nat_cond [X in X - _]big_nat_cond [X in _ - X]big_nat_cond.
rewrite sumnB// ⇒ i; rewrite andbT; exact: le.
Qed.
End SumsOverRanges.
In this section, we show how it is possible to equate the result of two sums performed
on two different functions and on different intervals, provided that the two functions
match point-wise.
Consider two equally-sized intervals
[t1, t1+d)
and [t2, t2+d)
...
Assume that the two functions match point-wise with each other, with the points taken
in their respective interval.
Lemma big_sum_eq_in_eq_sized_intervals:
\sum_(t1 ≤ t < t1 + d) F1 t = \sum_(t2 ≤ t < t2 + d) F2 t.
Proof.
induction d; first by rewrite !addn0 !big_geq.
rewrite !addnS !big_nat_recr ⇒ //; try by lia.
rewrite IHn //=; last by move⇒ g G_LTl; apply (equal_before_d g); lia.
by rewrite equal_before_d.
Qed.
End SumOfTwoIntervals.
\sum_(t1 ≤ t < t1 + d) F1 t = \sum_(t2 ≤ t < t2 + d) F2 t.
Proof.
induction d; first by rewrite !addn0 !big_geq.
rewrite !addnS !big_nat_recr ⇒ //; try by lia.
rewrite IHn //=; last by move⇒ g G_LTl; apply (equal_before_d g); lia.
by rewrite equal_before_d.
Qed.
End SumOfTwoIntervals.
In this section, we relate the sum of items with the sum over partitions of those items.
x_to_y is the mapping from an item to the partition it is contained in.
We prove that summation of f x over all x is less than or equal to the summation of
sum_of_partition over all partitions.
Lemma sum_over_partitions_le :
\sum_(x <- xs | P x) f x
≤ \sum_(y <- ys) sum_of_partition y.
Proof.
rewrite /sum_of_partition.
induction xs as [| x' xs' LE_TAIL]; first by rewrite big_nil.
have P_HOLDS: ∀ i j, true → P j && (x_to_y j== i) → P j by move⇒ ??? /andP [P_HOLDS _].
have IN_ys: ∀ x : X, x \in xs' → x_to_y x \in ys.
{ by move⇒ ??; apply H_no_partition_missing ⇒ //; rewrite in_cons; apply /orP; right. }
move: LE_TAIL; rewrite (exchange_big_dep P) ⇒ //= LE_TAIL.
rewrite (exchange_big_dep P) //= !big_cons.
case: (P x') ⇒ //=; last by apply LE_TAIL.
apply leq_add ⇒ //; last by apply LE_TAIL.
rewrite big_const_seq iter_addn_0.
apply leq_pmulr; rewrite -has_count.
apply /hasP; eapply ex_intro2 ⇒ //.
by apply H_no_partition_missing, mem_head.
Qed.
\sum_(x <- xs | P x) f x
≤ \sum_(y <- ys) sum_of_partition y.
Proof.
rewrite /sum_of_partition.
induction xs as [| x' xs' LE_TAIL]; first by rewrite big_nil.
have P_HOLDS: ∀ i j, true → P j && (x_to_y j== i) → P j by move⇒ ??? /andP [P_HOLDS _].
have IN_ys: ∀ x : X, x \in xs' → x_to_y x \in ys.
{ by move⇒ ??; apply H_no_partition_missing ⇒ //; rewrite in_cons; apply /orP; right. }
move: LE_TAIL; rewrite (exchange_big_dep P) ⇒ //= LE_TAIL.
rewrite (exchange_big_dep P) //= !big_cons.
case: (P x') ⇒ //=; last by apply LE_TAIL.
apply leq_add ⇒ //; last by apply LE_TAIL.
rewrite big_const_seq iter_addn_0.
apply leq_pmulr; rewrite -has_count.
apply /hasP; eapply ex_intro2 ⇒ //.
by apply H_no_partition_missing, mem_head.
Qed.
Consider a partition y'.
We prove that the sum of items excluding all items from a partition y'
is less-than-or-equal to the sum over all partitions except y'.
Lemma reorder_summation : \sum_(x <- xs | P x && (x_to_y x != y')) f x ≤
\sum_(y <- ys | y != y') sum_of_partition y.
Proof.
rewrite (exchange_big_dep (fun x ⇒P x && (x_to_y x != y'))) //=.
- rewrite big_seq_cond [X in _ ≤ X]big_seq_cond.
apply leq_sum ⇒ x' /andP [ARRo /andP [Px' NEQ]].
rewrite (big_rem (x_to_y x')) //=.
rewrite Px' eq_refl NEQ andTb andTb leq_addr //.
by apply H_no_partition_missing.
- move ⇒ y_of_x' x' /negP NEQ /andP [EQ1 /eqP EQ2].
rewrite EQ1 Bool.andb_true_l; apply/negP; intros CONTR.
apply: NEQ; clear EQ1.
by rewrite -EQ2.
Qed.
\sum_(y <- ys | y != y') sum_of_partition y.
Proof.
rewrite (exchange_big_dep (fun x ⇒P x && (x_to_y x != y'))) //=.
- rewrite big_seq_cond [X in _ ≤ X]big_seq_cond.
apply leq_sum ⇒ x' /andP [ARRo /andP [Px' NEQ]].
rewrite (big_rem (x_to_y x')) //=.
rewrite Px' eq_refl NEQ andTb andTb leq_addr //.
by apply H_no_partition_missing.
- move ⇒ y_of_x' x' /negP NEQ /andP [EQ1 /eqP EQ2].
rewrite EQ1 Bool.andb_true_l; apply/negP; intros CONTR.
apply: NEQ; clear EQ1.
by rewrite -EQ2.
Qed.
In this section, we prove a stronger result about the equality between
the sum over all items and the sum over all partitions of those items.
In order to prove the stronger result of equality, we additionally
assume that the sequences xs and ys are sets, i.e., that each
element is contained at most once.
We prove that summation of f x over all x is equal to the summation of
sum_of_partition over all partitions.
Lemma sum_over_partitions_eq :
\sum_(x <- xs | P x) f x
= \sum_(y <- ys) sum_of_partition y.
Proof.
rewrite /sum_of_partition.
induction xs as [|x' xs' LE_TAIL]; first by rewrite big_nil big1_seq //= ⇒ ??; rewrite big_nil.
rewrite //= in LE_TAIL; feed_n 2 LE_TAIL.
{ by move ⇒ ??; apply H_no_partition_missing; rewrite in_cons; apply /orP; right. }
{ by move: H_xs_unique; rewrite cons_uniq ⇒ /andP [??]. }
rewrite (exchange_big_dep P) //=; last by move⇒ ??? /andP[??].
rewrite !big_cons.
destruct (P x'); last by rewrite LE_TAIL (exchange_big_dep P) //=; move⇒ ??? /andP[??].
have → : \sum_(i <- ys | true && ( x_to_y x' == i)) f x' = f x'.
{ rewrite //= -big_filter.
have → : [seq i <- ys | x_to_y x' == i] = [:: x_to_y x']; last by rewrite unlock //= addn0.
have → : [seq i <- ys | x_to_y x' == i] = [seq i <- ys | i == x_to_y x'].
{ clear H_no_partition_missing LE_TAIL.
induction ys as [| y'' ys' LE_TAILy]; first by done.
feed LE_TAILy; first by move: H_ys_unique; rewrite cons_uniq ⇒ /andP [??].
by rewrite //= LE_TAILy //= eq_sym. }
apply filter_pred1_uniq ⇒ //.
by apply H_no_partition_missing; rewrite in_cons; apply /orP; left. }
apply /eqP; rewrite eqn_add2l; apply /eqP.
by rewrite LE_TAIL (exchange_big_dep P) //=; move⇒ ??? /andP[??].
Qed.
End Equality.
End SumOverPartitions.
\sum_(x <- xs | P x) f x
= \sum_(y <- ys) sum_of_partition y.
Proof.
rewrite /sum_of_partition.
induction xs as [|x' xs' LE_TAIL]; first by rewrite big_nil big1_seq //= ⇒ ??; rewrite big_nil.
rewrite //= in LE_TAIL; feed_n 2 LE_TAIL.
{ by move ⇒ ??; apply H_no_partition_missing; rewrite in_cons; apply /orP; right. }
{ by move: H_xs_unique; rewrite cons_uniq ⇒ /andP [??]. }
rewrite (exchange_big_dep P) //=; last by move⇒ ??? /andP[??].
rewrite !big_cons.
destruct (P x'); last by rewrite LE_TAIL (exchange_big_dep P) //=; move⇒ ??? /andP[??].
have → : \sum_(i <- ys | true && ( x_to_y x' == i)) f x' = f x'.
{ rewrite //= -big_filter.
have → : [seq i <- ys | x_to_y x' == i] = [:: x_to_y x']; last by rewrite unlock //= addn0.
have → : [seq i <- ys | x_to_y x' == i] = [seq i <- ys | i == x_to_y x'].
{ clear H_no_partition_missing LE_TAIL.
induction ys as [| y'' ys' LE_TAILy]; first by done.
feed LE_TAILy; first by move: H_ys_unique; rewrite cons_uniq ⇒ /andP [??].
by rewrite //= LE_TAILy //= eq_sym. }
apply filter_pred1_uniq ⇒ //.
by apply H_no_partition_missing; rewrite in_cons; apply /orP; left. }
apply /eqP; rewrite eqn_add2l; apply /eqP.
by rewrite LE_TAIL (exchange_big_dep P) //=; move⇒ ??? /andP[??].
Qed.
End Equality.
End SumOverPartitions.
We observe a trivial monotonicity-preserving property with regard to
leq.
Consider any type of indices, any predicate, ...
Consider any set of indices ...
Lemma sum_leq_mono :
monotone leq f.
Proof.
move⇒ x y LEQ.
rewrite /f big_seq_cond [in X in _ ≤ X]big_seq_cond.
apply: leq_sum ⇒ i /andP [IN _].
by apply: H_mono.
Qed.
End Monotonicity.
monotone leq f.
Proof.
move⇒ x y LEQ.
rewrite /f big_seq_cond [in X in _ ≤ X]big_seq_cond.
apply: leq_sum ⇒ i /andP [IN _].
by apply: H_mono.
Qed.
End Monotonicity.